New records and species of Pseudogaurax Malloch, 1915 (Diptera: Chloropidae) from the Amazon basin - Marques, Carla De Oliveira; Riccardi, Paula Raile; Ale-Rocha, Rosaly (Zootaxa, 2022)
Pseudogaurax Malloch is a speciose genus of Chloropidae in the Neotropical region. The South American fauna is understudied, particularly in the Amazon basin. Here we provide a taxonomic revision of the Amazonian species of Pseudogaurax, including the description of five new species—P. flaviscutellatus sp. nov., P. infulatus sp. nov., P. longitriangularis sp. nov., P. pallidus sp. nov. and P. poseidoni sp. nov.—and a key to all Brazilian species. Including our results, Pseudogaurax is known from 19 species from Brazil, 10 of which occur in the Amazon Forest.